1976
DOI: 10.1073/pnas.73.6.1773
|View full text |Cite
|
Sign up to set email alerts
|

A van der Waals-type equation of state for fluids with associating molecules

Abstract: The basic assumptions of van der Waals theory are contained in two well-known concepts: excluded volume (repulsive forces) and a homogeneous, isotropic field potential (attractive forces). We have superimposed on these, one more well-known concept: the existence of dimers, trimers, etc., at chemical equilibrium. With Following the basic concepts of van der Waals, we postulate that when nT moles of fluid occupy volume V at temperature T, the pressure P can be expressed by P = Phs + Pa t [1] where subscript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
82
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(84 citation statements)
references
References 9 publications
2
82
0
Order By: Relevance
“…Panayiotou (1 989, 1990) combined chemical theory into the Sanchez-Lacombe equation of state (Sanchez and Lacombe, 1976;Lacombe and Sanchez, 1976), a lattice fluid theory, to describe thermodynamic properties and phase equilibria of pure alcohols and mixtures of alcohols with alkanes. His hydrogen bonding expressions are similar to those derived by Heidemann and Prausnitz (1976) and by Ikonomou and Donohue (1986).…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…Panayiotou (1 989, 1990) combined chemical theory into the Sanchez-Lacombe equation of state (Sanchez and Lacombe, 1976;Lacombe and Sanchez, 1976), a lattice fluid theory, to describe thermodynamic properties and phase equilibria of pure alcohols and mixtures of alcohols with alkanes. His hydrogen bonding expressions are similar to those derived by Heidemann and Prausnitz (1976) and by Ikonomou and Donohue (1986).…”
Section: Introductionsupporting
confidence: 63%
“…When physical interactions are considered, the equations for chemical equilibria and physical equilibria usually are solved simultaneously by a trial-and-error procedure. Heidemann and Prausnitz (1976) showed that it is possible to solve for the chemical equilibria analytically and combine the results into the equation of state to solve for phase equilibria.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to satisfy this last condition, and the considerations of an infinite equilibrium model, Heidemann and Prausnitz (1976) developed a new mixing rule as follows considering this series of equilibria:…”
Section: A+b-abmentioning
confidence: 99%